2018
DOI: 10.1002/ejoc.201801167
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Oxazinoindolones via Regioselective 6‐exodig Iodolactonization

Abstract: An efficient protocol for facile construction of 3,4-dihydro-10-iodo-3-iodomethylene-[1,4]oxazino[4,3-a]indol-1-ones has been developed by using a regio-and stereoselective iodolactonization reaction. Subsequent palladium cross-coupling reactions of 3,4-dihydro-10-iodo-3-iodomethylene-[1,4]-oxazino[4,3-a]indol-1-ones readily afforded functionalized oxazinoindolones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…5-Hydroxytryptamine (5-HT) with an indole core is an important synthon that plays a crucial role in serotonin receptors . In light of this, we embarked on extending our amidative exo -cyclization to N -propargyl indole-2-carboxylate S9 . Unfortunately, the reaction with benzylamine produced only 7% of the desired product 9a .…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5-Hydroxytryptamine (5-HT) with an indole core is an important synthon that plays a crucial role in serotonin receptors . In light of this, we embarked on extending our amidative exo -cyclization to N -propargyl indole-2-carboxylate S9 . Unfortunately, the reaction with benzylamine produced only 7% of the desired product 9a .…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the other hand, the THP-protected propargyl bromo derivative 14 was obtained in good overall yield from propargyl alcohol 11 in three steps following a reported procedure . Following the established protocol, the key intermediate 16 was obtained in 77% yield, as shown in Scheme . Preparation of intermediate 17 from 16 was expected via a direct tandem amidative exo -cyclization with NH 3 in MeOH (7.0 M) as an amine source using 0.4 equiv of TBD as in the case of the synthesis of 10a .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study dedicated to the synthesis and evaluation of tricyclic heterocycles as oxazolidinones as potential inhibitors of Mycobacterium tuberculosis UDP-galactopyranose mutase (Mt UGM), an enzyme involved in the biosynthesis of the galactan moiety of the cell wall, Thiery prepared various oxazinoindolones 45 from the iodolactonization of Npropargylindoles 44 [35,36] (Scheme 19). It was demonstrated that the iodolactonization was very effective with electron-rich and electron-poor substituents on indoles and tolerated alkyl and aromatic substituents on the alkyne triple bond (R 1 = Me, Ph).…”
Section: Scheme 18 Synthesis Of Oxazinoindolones 43mentioning
confidence: 99%
“…Stille coupling was performed using an organotin compound and a catalytic amount of dichlorobis(acetonitrile)palladium(II) in DMF at 40 • C (Scheme 8) [54,55]. Under these conditions, the coupling with compound 7a was successfully achieved, and two examples of coupling products (11b and 11c) were obtained in low to moderate yields (35-40%).…”
Section: Stille Reaction On the 1-benzyl-3-iodo-1h-indole-2-carbonitrile Derivativesmentioning
confidence: 99%